A Note on the Name “Sinnaces” and Armenian Claims on an Assyrian Royal Background - Richardson, Seth (Anabasis. Studia Classica et Orientalia, 2017)
Three separate men bearing the princely name “Sinnaces” are mentioned by Josephus, Plutarch, and Tacitus in various tales of Partho-Armenian dynastic intrigues. The origin of the name is obscure, but this note proposes that it derives from the name of the Assyrian king Sennacherib (r. 705–681 BC), one of a number of Late Antique and medieval Armenian references to a supposed Assyrian background to its royal line.